Planificación tributaria y su relación con la rentabilidad en la Empresa A y B La Mona Amazónica S.A.C. Iquitos 2024 - Castillo Orellana, Renso Sebastian (2025)
This study aimed to determine the relationship between tax planning and profitability in company A and B La Mona Amazónica S.A.C. year 2024, a quantitative approach was used, employing a descriptive and non experimental design, to observe and describe the variables without manipulation, as well as a correlational design to identify the degree of existing relationship. Spearman's correlation between both variables is 0.790**, with sig.=0.000**, which is statistically significant. This allowed us to accept the hypothesis of the relational existence between the variables under study. This finding provides a practical approach to improve the strategy regarding tax planning and the profitability of the company in a given period or fiscal year.